MODEL PEMBERDAYAAN PETANI UBIKAYU MELALUI POLA KLASTER SISTEM AGRIBISNIS TERINTEGRASI DI KABUPATEN SUKABUMI PROVINSI JAWA BARAT - Himmatul Miftah; Ahmad Syarbaini (Universitas Sebelas Maret, 2014)
The research was aimed at developing a society empowerment model through a cluster pattern. Empowerment was able to increase income through the optimization of farming resources to produce processed cassava products with high selling and added values. The model was developed by the integration of upstream and downstream agribusiness subsystems by using a cluster pattern that involved various components including farmers/farmer groups, processes in agribusiness system, and institutional system in cassava agribusiness in Sukabumi Regency.